Revisiting Migrant Networks
VIII, 236 p. 1 illus.
Keywords: This open access book provides new conceptualisations on the networks of migrants and their descendants in accessing the labour market. Although references to social networks are common in discussions of migration, simplified ideas of co-ethnic networks often obscure the reality, for example confounding ties with co-ethnics and ‘strong ties’. This open access book addresses key questions about the role of networks in migration contexts, particularly in relation to how migrants and their descendants, access the labour market and develop their employment trajectories over time. Rather than adopting a narrow essentializing ethnic lens, the research presented in this book explores intersectional identities of class, generation and gender. By focusing on the kinds of capital circulating between ties, including the dark side of social capital, the book offers insights into power dynamics and the potentially exclusionary dimension of networks. Taking a long term view, acrossgenerations, the research in this book shows how migrants and their descendants mobilize resources to tackle discrimination and enhance their position within particular labour markets. Drawing on robust quantitative and rich qualitative data, this book provides a primary source to students, scholars and policy-makers focusing on issues of migration, social networks, social mobility as well as labour market inequalities.